Pedigree and Panache A History of the Art Auction in Australia - Huda, Shireen (ANU Press, 2008)
Art auctions have long captured the public imagination. They regularly make news headlines and have become synonymous with glamour, money and social distinction. The marketing of auction houses and the works they sell has resulted in firms attaining authoritative positions and the ability both to influence and reflect collecting tastes. Pedigree and Panache is the first comprehensive history of the art auction in Australia. In this fascinating work, Shireen Huda investigates the construction of the glamorous reputation of art auctions and art auction houses. Featuring absorbing case studies of key art auctions and major art auction houses in Australia (including Christie's, Sotheby's and Deutscher-Menzies) the work provides an overview of the origin and international development of art auctions. The development of the Australian marketplace is then explored, detailing colonial inception and continuing until Christie's withdrawal of its saleroom presence in 2006. This book is an engaging read for those involved in the art industry, as well as historians, artists, collectors and anyone interested in the art market, art investment, social history and art history.